GERAKAN DIGITAL MELAWAN COVID-19 DI KELURAHAN CIWEDUS KECAMATAN CILEGON KOTA CILEGON PROVINSI BANTEN - Hilman, Mohamad (Universitas Sultan Ageng Tirtayasa, 2021)
Ciwedus is one of the villages located in Cilegon District, Cilegon City, BantenProvince. In the south with Bagendung, in the west with Ciwaduk, in the east withthe Dam, and in the west directly with Citangkil. The threat of the Covid-19 virusrequires a rapid response to prevent continuous transmission. Strategic steps areneeded to break the chain of transmissionof theCovid-19 virus, generallyinIndonesia and especially in the Ciwedus village, one of which is educating thepublic throughtheDigitalMovementAgainstCovid-19.breakthroughsorcreativeideas used in the 2021 thematic Online KKM group, namely the Design with theDigital Movement Against Covid-19 in the form of poster and video publicationsonsocialmedia